Magnetic transition and spin dynamics in the triangular Heisenberg antiferromagnet α-KCrO2 - Xiao, F.; Lancaster, T.; Baker, P.J.; Pratt, F.L.; Blundell, S.J.; Möller, J.S.; Ali, N.Z.; Jansen, M. (Physical review B - Condensed Matter and Materials Physics, 2013)
We present the results of muon-spin relaxation measurements on the triangular lattice Heisenberg antiferromagnet α -KCrO 2 . We observe sharp changes in behavior at an ordering temperature of T c =23 K, with an additional broad feature in the muon-spin relaxation rate evident at T=13 K, both of which correspond to features in the magnetic contribution to the heat capacity. This behavior is distinct from both the Li- and Na-containing members of the series. These data may be qualitatively described with the established theoretical predictions for the underlying spin system.
EPrint Processing Status: Full text deposited in DRO